2023
DOI: 10.1097/mcp.0000000000000938
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between tuberculosis and chronic obstructive pulmonary disease

Abstract: Purpose of reviewOur objective was to review the current literature regarding socioeconomic, environmental, clinical, and immunologic factors common to chronic obstructive pulmonary disease (COPD) and tuberculosis (TB). Recent findingsRecent studies suggest that TB patients might be at increased risk for developing COPD. Conversely, additional prospective cohort studies have determined that COPD patients are at increased risk for active TB: a risk that appears to be partially mediated through inhaled corticost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…Previous observational studies have shown a strong association between COPD and TB, suggesting that both may be risk factors for each other [9,13,29,30]. Furthermore, in ammation and damage to the respiratory system caused by COPD can promote the infection of TB, and respiratory infections and in ammation may also play a role in the development and progression of COPD [31] [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies have shown a strong association between COPD and TB, suggesting that both may be risk factors for each other [9,13,29,30]. Furthermore, in ammation and damage to the respiratory system caused by COPD can promote the infection of TB, and respiratory infections and in ammation may also play a role in the development and progression of COPD [31] [32].…”
Section: Discussionmentioning
confidence: 99%